P105 A MARBLE IN THE HEART: A MYSTERIOUS MITRAL MASS. (18th May 2022) - Cosmi, D; Buccolieri, M; Capponi, E; Di Pasquale, T; Da Col, U; Murrone, A
Abstract: A 70–year–old woman came to our observation for acute heart failure during atrial fibrillation with high ventricular response. In the medical history she presented a previous radiofrequency ablation of paroxysmal supraventricular tachycardia, a previous episode of atrial fibrillation treated with electrical cardioversion, two hospitalizations for transient ischemic attack (TIA), the last two months before hospitalization . The patient had always refused the introduction of oral anticoagulant therapy. The transthoracic echocardiogram showed a rounded formation, with regular margins, of 20x19 mm, isoechoic and poorly mobile, adhered to the atrial side of the annulus and the posterior mitral flap, confirmed by the transesophageal echocardiogram (Fig 1, 2, 3 ). The formation did not result in mitral obstruction or significant mitral regurgitation. The left atrium appeared markedly dilated, with moderate spontaneous echo inside. In the left appendage there was no thrombus, and there were no other relevant findings. Markers of inflammation and serial blood cultures taken during hospitalization were negative, so bacterial endocarditis appeared unlikely. Mixoma or fibroelastoma appeared to be the most likely diagnosis. In consideration of the high risk of embolization and to clarify the diagnosis, the patient underwent cardiac surgery with exeresis of the formation (Fig 4–5), subsequent quadrangular resection of the posterior mitral flap, sliding and mitral annuloplasty. Macroscopically, the mass appeared brownish–red, with a smooth surface, solid and compact consistency. The histological analysis showed red blood cells and platelets mixed with vessels and granulation tissue; the wall of the mass was made up of connective tissue. Based on the findings, the differential diagnosis was between a blood cyst or a native mitral valve thrombosis. Blood cysts are generally congenital and disappear spontaneously in childhood, rarely occurring in adults. They are fluid or semi–fluid formations, and ultrasonographically they appear as masses with anechoic or hypoechoic content, surrounded by a thin wall. Thrombosis on native mitral valve is also an infrequent event, but described in literature, particularly in the presence of hypercoagulative states, mitral stenosis, atrial fibrillation. Based on the characteristics of the mass, we believe that the most likely hypothesis is that of a rare case of thrombosis on a native mitral valve.